Discovery of a stripped red giant core in a bright eclipsing binary system - Maxted, P. F. L.; Anderson, D. R.; Burleigh, M. R.; Cameron, A. Collier; Heber, Ulrich; Gaensicke, B. T.; Geier, Stephan; Kupfer, Thomas; Marsh, T. R.; Nelemans, Gijs; O'Toole, S. J.; Ostensen, R. H.; et al. (Monthly Notices of the Royal Astronomical Society, 2011)
We have identified a star in the Wide Angle Search for Planets (WASP) archive photometry with an unusual light curve due to the total eclipse of a small, hot star by an apparently normal A-type star and with an orbital period of only 0.668d. From an analysis of the WASP light curve together with V-band and IC-band photometry of the eclipse and a spectroscopic orbit for the A-type star we estimate that the companion star has a mass of 0.23 ± 0.03M⊙ and a radius of 0.33 ± 0.01R⊙, assuming that the A-type star is a main-sequence star with the metallicity appropriate for a thick-disc star. The effective temperature of the companion is 13400 ± 1200K from which we infer a luminosity of 3 ± 1L⊙. From a comparison of these parameters to various models we conclude that the companion is most likely to be the remnant of a red giant star that has been very recently stripped of its outer layers by mass transfer on to the A-type star. In this scenario, the companion is currently in a shell hydrogen-burning phase of its evolution, evolving at nearly constant luminosity to hotter effective temperatures prior to ceasing hydrogen burning and fading to become a low-mass white dwarf composed of helium (He-WD). The system will then resemble the pre-He-WD/He-WD companions to A- and B-type stars recently identified from their Kepler satellite light curves (KOI-74, KOI-81 and KIC10657664). This newly discovered binary offers the opportunity to study the evolution of a stripped red giant star through the pre-He-WD stage in great detail. © 2011 The Authors Monthly Notices of the Royal Astronomical Society © 2011 RAS.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: close; Binaries: eclipsing; Binaries: spectroscopic; Stars: individual: 1SWASPJ024743.37-251549.2; Stars: peculiar